2011
DOI: 10.1111/j.1872-034x.2011.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of remnant spleen volume on the progression of steatohepatitis in diet‐induced obese rats after a splenectomy

Abstract: These results indicate the importance of preserving splenic tissue. This residual spleen may play an important role in preventing the progression from diet-induced hepatic steatosis to steatohepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Reports of the relationship between the spleen and lipid metabolism have emerged: splenectomized rodents showed high cholesterol levels (21), hyperlipidemia (22), and increased intrahepatic fat accumulation (23). Elucidating the kinetics of iron in diabetes and other diseases is expected to lay the foundation for novel irontargeting therapies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of the relationship between the spleen and lipid metabolism have emerged: splenectomized rodents showed high cholesterol levels (21), hyperlipidemia (22), and increased intrahepatic fat accumulation (23). Elucidating the kinetics of iron in diabetes and other diseases is expected to lay the foundation for novel irontargeting therapies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics are frequently clustered as metabolic syndrome, a major cause of T2D onset in humans [16]. Alterations in immune function have also been observed in MSG-treated obese rats, including splenic dysfunctions [17,18]. Since recent studies suggest that the spleen participates in metabolic and immunological abnormalities present in obesity [17,19,20], the aim of the present study was to evaluate the effect of splenectomy in the hypothalamic obesity induced by neonatal MSG treatment.…”
Section: Introductionmentioning
confidence: 97%
“…Our data was consistent with previous studies. [ 8 9 26 ] And, we demonstrated that splenectomy worsened metabolism of TC, LDL, and VLDL, in animals fed either a normal or high-fat diet. Some theories have been raised to explain the possible mechanism of splenic regulation of lipid metabolism.…”
Section: Discussionmentioning
confidence: 73%
“…[ 26 ] Interestingly, compared with the total splenectomy, partial splenectomy and hemisplectomy have been shown to result in more diminished lipid dysregulation, suggesting a direct correlation between spleen volume and function. [ 8 9 27 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation